1995
DOI: 10.1159/000188615
|View full text |Cite
|
Sign up to set email alerts
|

Iron Depletion in the Remnant Kidney

Abstract: Urinary and proximal tubular iron are increased after subtotal nephrectomy, and iron depletion has been shown to be beneficial in proteinuric models of chronic renal disease in rats. In this study, iron depletion by low iron pair-fed diet and periodic phlebotomy was induced for 6 months in rats with partial (5/6) nephrectomy, resulting in a reduction in hematocrit and serum iron in all iron-deficiency subgroups. Tubular iron, assessed by energy dispersive analysis and electron microscopy, was reduced in quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…This salutary effect of iron restriction on renal damage is consistent with the results previously reported in the different models of renal disease [20,21]. However, our observation differs from a previous report of remnant kidney model rats, in which iron restriction did not have protective effects on renal damage [22]. There are two plausible explanations for what appear to be conflicting data.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This salutary effect of iron restriction on renal damage is consistent with the results previously reported in the different models of renal disease [20,21]. However, our observation differs from a previous report of remnant kidney model rats, in which iron restriction did not have protective effects on renal damage [22]. There are two plausible explanations for what appear to be conflicting data.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, it is conceivable that the differences may be caused by differences in the experimental protocol. Nankivell and Harris [22] provided iron restriction and periodic phlebotomy before surgery or throughout the experiment, whereas we supplied just only iron restriction from 1 week after surgery in CKD rats. In this study, we found a beneficial effect of dietary iron restriction on renal damage and hypertension in a rat model of CKD through the inhibition of renal mineralocorticoid receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…36,62 In addition, kidney and urinary iron content is increased in patients 3,17,[63][64][65][66][67][68][69][70][71] and animal models of AKI and CKD. 3,6,14,[71][72][73][74][75][76][77][78][79][80] Finally, the severity of kidney injury can be reduced by iron-deficient diets, the use of iron chelators or treatment directed at reducing iron-related oxidative stress in animal models. 3,15,19,71,79,[81][82][83] Direct evidence of renal toxic effects of iron is, however, limited in humans.…”
Section: Iron-induced Kidney Injurymentioning
confidence: 99%
“…One study analyzed selected homogenized brain portions and found correlations between Gd and Fe concentrations after administration of linear GBCAs 42 . However, the rats in this study were subtotally nephrectomized, which impairs renal elimination of the GBCA, and moreover causes severe urinary Fe loss 60 …”
Section: Discussionmentioning
confidence: 90%
“…42 However, the rats in this study were subtotally nephrectomized, which impairs renal elimination of the GBCA, and moreover causes severe urinary Fe loss. 60 From visual inspection of Gd-Fe overlay images after gadodiamide, a rather weak colocalization could be surmised in the OB, in the DCN, and in the IC. On the other hand, distinctive distribution patterns of both Fe and Gd were determined, respectively, but found not to be congruent, for example, in the Hi and the GrCb.…”
Section: Colocalization Of Gadolinium With Iron Manganese and Endothe...mentioning
confidence: 97%